Bifidobacterium breve M‐16V as a Probiotic for Preterm Infants: A Strain‐Specific Systematic Review. Issue 4 (19th December 2017) - Athalye‐Jape, Gayatri; Rao, Shripada; Simmer, Karen; Patole, Sanjay
Abstract: Introduction: Bifidobacterium breve M‐16V has been used as a probiotic in preterm infants. Probiotic strain‐specific data are essential to guide clinical practice. Objective : To assess effects of B breve M‐16V in preterm neonates. Design : A systematic review of randomized controlled trials (RCTs) and non‐RCTs of B breve M‐16V in preterm infants was conducted. Multiple databases, proceedings of Pediatric Academy Society, and other relevant conferences were searched in September 2016 and on January 5, 2017. Results : Five RCTs (n = 482) and 4 non‐RCTs (n = 2496) were included. Of the 5 RCTs, 4 carried high/unclear risk of bias in many domains. Meta‐analysis (fixed effects model) of RCTs showed no significant benefits on stage ≥2 necrotizing enterocolitis, late‐onset sepsis, mortality, and postnatal age at full feeds. Meta‐analysis of non‐RCTs showed significant benefits on (1) late‐onset sepsis—3 studies (n = 2452), odds ratio = 0.56 (95% CI, 0.45–0.71), P < .0001; (2) mortality—2 studies (n = 2319), odds ratio = 0.61 (95% CI, 0.44–0.84), P = .002; and (3) postnatal age at full feeds (days)—2 studies (n = 361), mean difference, −2.42 (95% CI, −2.55 to −2.3), P < .00001. There were no adverse effects from B breve M‐16V. On Grading of Recommendations, Assessment, Development, and Evaluation analysis, the overall quality of evidence was deemed very low. Conclusions : Current evidence is limited regarding the potential of B breve M‐16V in preterm neonates. Adequately powered, preferably cluster RCTs are needed to confirm these findings.